Design and Evaluation of Nanoparticulate Drug Delivery Systems for Imaging and Treatment of Malignant Brain Tumor (Global Journal of Science Frontier Research, 2014)
Malignant brain tumours are one of the most devastating human cancers associated with high mortality and morbidity rates. The median survival of malignant glioma patie-nts ranges between 3 and 16 months and has virtually rema-ined unchanged during the last 3 decades. Difficulties in early detection, local recurrence, and resistance to conventional therapies are the major reasons for failure in malignant brain tumour treatment. The therapy of malignant gliomas is further limited by the inadequate delivery of therapeutic agents to the brain due to the presence of the blood-brain barrier, blood-brain-tumor barrier as well as non-specificity targeting. Nanoparticles (NPs) have drawn increased interest in treating malignant brain tumours due to their potential to act as a vector for brain delivery and to provide tumourspecific detection and treatment. If designed appropriately, NPs may act as a drug vehicle able to target tumor tissues or cells, and protect the drug from inactivation during its transport. The aim of this article was to provide brief overview of nanoparticulate drug delivery systems for imaging and treatment of brain cancer and to evaluate their safety in clinical use. Besides invasive physical methods to bypass or disrupt the BBB and/or BBTB, other methods like pharmacological and physio-logic approach are possible.
Keywords: nanoparticulate; nanoparticle; nanovectors; nanomedicine; nanoparticulate drug delivery system